PENGARUH PIUTANG, PERSEDIAAN DAN BIAYA ADMINISTRASI UMUM TERHADAP LABA PADA PT. KARYA UTAMA - Susi Marni,; Savriadi,; Tina Arfah, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This research is conducted to examine the effect of receivable variable, inventory, and general administration cost to earnings at manufacturing company in BEI. Based on the type of data, this research includes quantitative research because the data used in the form of numbers. The data used in this research were obtained from manufacturing companies in BEI, data required in the form of annual financial statements (published report) by companies, journals and other literatures that related with the object of the research. Method of data analysis that used in this research is multiple regression method (multiple regressions). Data processing using statistical software package for social sciences (SPSS) version 16. The data were analyzed by descriptive statistic test, classic assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test) and hypothesis testing (T test, and F test). Based on the results of the analysis that partial inventory has an effect but not significant to profit at the level of significance more than 5%. Partial accounts receivable has an effect but not significant to profit at level of significance more than 5%. Also for variable general administrative costs show of insignificant results on earnings at level of significance above 5%. Based on the results of simultaneous, testing results obtained that account receivables, inventories and general administrative costs have an effect but not significant simultaneously to earnings. This means that these three independent variables (account receivables, inventories and general administrative costs) have an influence but not significant to the dependent variable (profit).